Effects of Predisposing, Enabling, and Reinforcing Factors on Completeness of Child Immunization in Pamekasan, Madura - Nur Jayanti; Endang Sutisna Sulaeman; Ety Poncorini Pamungkasari (Masters Program in Public Health, 2017)
Background: According to WHO Weekly Epidemiological Record, Indonesia ranked fourth the lowest country in immunization coverage after India, Nigeria, and Democratic Republic of Congo. Likewise, Pamekasan District in Madura was one of districs in East Java with the lowest immunization coverage. This study aimed to determine the effects of predisposing, enabling, and reinforcing factors on completeness of child immunization, using PRECEDE and PROCEED model and health belief model.Subjects and Method: This was an observational analytic study with case control design. This study was carried out at 4 community health centers in Pamekasan District, Madura, East Java, in March to April, 2017. A sample of 135 mothers who had infants aged 10 to 12 months were selected for this study by fixed disease sampling. The dependent variable was completeness of immunization use. The independent variables were maternal education, attitude towards immunization, perceived susceptibility, perceived severity, perceived benefit, perceived barrier, self efficacy, family support, and distance to health service. The data were collected by questionnaire and analyzed using path analysis.Results: Perceived barrier (b= -0.5; 95% CI = -1.5 to 0.4; p= 0.255) and distance to health service (b= -1.0; 95% CI= -2.0 to -0.1; p= 0.037) had a negative effect on completeness of immunization. Perceived susceptibility (b= 1.1; 95% CI= 0.2 to 2.0; p= 0.022), perceived severity (b= 1.5; 95% CI= 0.5 to 2.5; p= 0.003), perceived benefit (b= 0.7; 95% CI= -0.1 to 1.6; p= 0.110), and self efficacy (b= 0.6; 95% CI= -0.3 to 1.5; p= 0.193) had a positive effect on completeness of immunization. Perceived susceptibility was affected by maternal education (b= 1.0; 95% CI= 0.3 to 1.7; p= 0.005). Perceived severity was affected by maternal education (b= 0.9; 95% CI= 0.5 to 1.6; p= 0.018) and attitude towards immunization (b= 1.0; 95% CI= 0.3 to 1.8; p= 0.007). Perceived benefit was affected by family support (b= 0.7; 95% CI= -0.1 to 1.4; p= 0.078). Likeliwise, self efficacy was affected by family support (b= 0.6; 95% CI = 0.1 to 1.3; p= 0.134).Conclusion: Perceived barrier and distance to health service have a negative effect on completeness of immunization. Perceived susceptibility, perceived severity, perceived benefit, and self efficacy have a positive effect on completeness of immunization.Keywords: completeness of immunization, PRECEDE and PROCEED model, health belief modelCorrespondence: Nur Jayanti. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: Yanti_nurjayanti13@yahoo.co.id. Mobile: +6282233829768.Journal of Epidemiology and Public Health (2017), 2(2): 106-118https://doi.org/10.26911/jepublichealth.2017.02.02.02